2004
DOI: 10.4049/jimmunol.172.10.6080
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor-2/6 Agonist Macrophage-Activating Lipopeptide-2 Cooperates with IFN-γ to Reverse the Th2 Skew in an In Vitro Allergy Model

Abstract: Dendritic cells (DC) are the most potent APCs with the capacity to induce, modulate, or shut down immune function. These features make them potentially useful for treating diseases associated with misled immunologic responses. Therefore, it was the aim of this study to reverse the allergen-dependent Th2 reaction responsible for allergic symptoms by modulating DC function. This issue was addressed in an in vitro test system consisting of human monocyte-derived allergen-pulsed DC from allergics cocultured with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Generating DC from murine bone marrow CD34 + HPC has been used as an alternative, but this procedure is time-consuming and requires a significant number of animals. The establishment of human in vitro models of DC had offered the possibility to demonstrate that haptens were able to directly activate cultured DC derived from peripheral blood monocytes or from CD34 + HPC (Aiba et al, 1997;Degwert et al, 1997;Rougier et al, 2000;De Smedt et al, 2001;Weigt et al, 2004). Several studies confirmed these observations showing the upregulation of maturation markers (CD83, CD80, CD86, CD40) on human DC (Coutant et al, 1999;Aiba et al, 2000;Tuschl et al, 2000;Arrighi et al, 2001).…”
Section: Use Of Dcs To Identify Contact Allergenssupporting
confidence: 65%
“…Generating DC from murine bone marrow CD34 + HPC has been used as an alternative, but this procedure is time-consuming and requires a significant number of animals. The establishment of human in vitro models of DC had offered the possibility to demonstrate that haptens were able to directly activate cultured DC derived from peripheral blood monocytes or from CD34 + HPC (Aiba et al, 1997;Degwert et al, 1997;Rougier et al, 2000;De Smedt et al, 2001;Weigt et al, 2004). Several studies confirmed these observations showing the upregulation of maturation markers (CD83, CD80, CD86, CD40) on human DC (Coutant et al, 1999;Aiba et al, 2000;Tuschl et al, 2000;Arrighi et al, 2001).…”
Section: Use Of Dcs To Identify Contact Allergenssupporting
confidence: 65%
“…Although numerous reported epidemiological and experimental studies have demonstrated the inhibitory role of live or killed microbes or microbial components on allergic responses [18][19][20][21][22][23][24][25], the basis for this inhibition remains unclear. In particular, little experimental study has been performed on the effect and mechanism of neonatal microbial exposure on airway allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…MALP-2 can induce CD80 (B7-1), CD86 (B7-2), major histocompatibility complex I and II and CD40 expression in B cells and dendritic cells (DCs) [51,52]. Furthermore, MALP-2 has the ability to increase the release of interferon-γ (IFN-γ) from DCs in response to allergens [53]. Mucosal delivery of MALP-2 via the intratracheal route resulted in a marked decrease in AHR, eosinophilia and Th2 cytokines in a murine model of asthma [54].…”
Section: Tlr1 2 6 and 10mentioning
confidence: 99%